Bimetal MOF (Metal Organic Framework) material as well as preparation method and application thereof

Through the preparation of bimetal MOF materials, the problem of fluoride ion removal and detection in drinking water is solved, efficient adsorption and sensitive detection are achieved, and good renewability and anti-interference are suitable for deep removal and instantaneous drinking water. Test.

CN119285980APending Publication Date: 2025-01-10HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411521433.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove and detect fluorine ions in drinking water, and traditional fluorescent probes have problems such as high cost, complex operation and poor recyclability.

Method used

Using bimetallic MOF material, the organic lanthanum salt, organic iron salt and organic ligand are reacted in an organic solution through the preparation method to form a bimetallic MOF material with a micro-nano porous structure and a surface rich in hydroxyl and amino groups to achieve fluorine ions Adsorption and fluorescence detection.

Benefits of technology

It realizes efficient adsorption and sensitive detection of fluoride ions, with a maximum adsorption capacity of 400.860mg/g, a linear detection range of 0 to 80μM, and the material has good renewability and anti-multi-ion interference ability, which is suitable for deep removal of drinking water and Instant detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285980A_ABST
    Figure CN119285980A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic MOF material and a preparation method and application thereof. The preparation method comprises the following steps: dispersing organic lanthanum salt, organic ferric salt and organic ligand in an organic solution, stirring, and carrying out ultrasonic treatment to obtain a mixed solution; adding alkali into the mixed solution, and then carrying out ultrasonic treatment to obtain a precursor; heating the precursor in an oil bath, and naturally cooling after the reaction is finished; the reactants are separated, dried and ground into powder, and the bimetallic MOF material is obtained. The bimetallic MOF material has adsorption and fluorescence detection functions. The bimetal MOF material prepared by the method disclosed by the invention has very high adsorption capacity on fluorine ions in water, and the maximum adsorption capacity of the bimetal MOF material reaches 400.860 mg / g. And the detection limit of the linear range is 0-80 [mu] M.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of drinking water treatment, and in particular relates to a bimetallic MOF material and a preparation method and application thereof. Background Art

[0002] Drinking water safety is an important livelihood issue. Long-term intake of excessive fluoride may cause serious damage to human bones, kidneys, liver and brain, and even endanger life. In addition, because fluoride pollution is usually colorless and odorless, people cannot identify its presence through their senses. In view of the geographical dispersion, variable forms, unclear removal mechanism, and high difficulty and cost of treatment of fluoride pollution, the current relevant treatment technology foundation is relatively weak, and the deep removal and effective detection of fluoride in drinking water have not yet been achieved. Therefore, there is an urgent need to develop efficient and low-cost treatment and detection technologies.

[0003] Adsorption is widely considered to be one of the effective means to remove fluoride ion pollutants from water. Commonly used adsorption materials include metal organic frameworks (MOFs), metal oxides, double-layer metal hydroxides and porous carbon materials. Among them, MOF has attracted widespread attention due to its large specific surface area and rich surface functional groups. MOF is a crystalline composite material formed by coordination between metal ions or metal clusters and organic ligands. Its structure is composed of metal centers and organic molecules, and a highly structured network is formed through coordination bonds with metal ions. The regulation of these network arrangements can affect the formation of porous structures in MOF. In addition, the synthesis of bimetallic MOF is an effective method to improve the stability of the framework, catalytic activity and adsorption performance. Fluoride ions can be removed through electrostatic interactions with the MOF surface; at the same time, functional groups on the MOF surface, such as amino and hydroxyl groups, can promote the adsorption of fluoride ions, among which hydroxyl groups participate in ion exchange, while amino groups bind fluoride ions through hydrogen bonding. In addition, certain metal centers in MOF (such as iron, aluminum, lanthanum, etc.) can produce specific metal-fluorine interactions, thereby further removing fluoride ions from water.

[0004] Instrumental analysis methods rely on expensive equipment and complex operations in fluoride ion detection, which limits their practical application in point-of-care detection. In contrast, fluorescent probes have attracted much attention due to their advantages such as simple operation, high cost-effectiveness and user-friendliness, and are expected to become a point-of-care detection tool for fluoride ions. At present, luminescent organic compounds with fluorine-hydrogen bonds or fluorine-boron bonds have been widely used in fluoride ion detection, but their practical applications often have problems such as incompatibility with aqueous media and poor recyclability. In addition, these organic probes have limited effects on fluoride removal in aqueous media, due to problems such as small surface area, low solubility and non-porous nature. In recent years, functional group-modified fluorescent materials such as metal organic frameworks (MOFs), polymers and nanocomposites have provided new research directions for fluoride ion detection. Among them, fluorescent MOFs have shown good prospects in the detection and removal of fluoride ions due to their designable structure, easy modification of pores and large specific surface area. Summary of the invention

[0005] In view of the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a bimetallic MOF material and a preparation method and application thereof. The bimetallic MOF material has both adsorption and fluorescence detection functions, and the preparation method is simple and easy to implement.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a bimetallic MOF material comprises the following steps:

[0008] S1, dispersing an organic lanthanum salt, an organic iron salt and an organic ligand in an organic solution, stirring and ultrasonicating to obtain a mixed solution;

[0009] S2, adding alkali to the mixed solution, and then performing ultrasonic treatment to obtain a precursor;

[0010] S3, heating the precursor in an oil bath, and cooling it naturally after the reaction is completed;

[0011] S4. Separate, dry and grind the reactants into powder to obtain a bimetallic MOF material; the bimetallic MOF material has adsorption and fluorescence detection functions.

[0012] In a further embodiment, the organic lanthanum salt is at least one of lanthanum acetylacetonate and lanthanum isopropoxide;

[0013] The organic iron salt is at least one of ferrocenecarboxylic acid and ferroholly acid;

[0014] The organic ligand is at least one of 2-aminoterephthalic acid and 2-aminotrimesic acid.

[0015] In a further embodiment, the molar ratio of the organic lanthanum salt, the organic iron salt and the organic ligand is 1-5:1-5:2-10.

[0016] In a further embodiment, the alkali is aqueous ammonia or sodium hydroxide solution, and the pH of the mixed solution is adjusted to 7-11 after the alkali is added.

[0017] In a further embodiment, the organic solvent is DMF, ethanol and ethylene glycol.

[0018] In a further embodiment, in step S3, the oil bath is heated at a temperature of 80-120° C. for a time of 6-24 h.

[0019] In a further embodiment, in step S4, the separation is performed by centrifugation, and the drying temperature is 60-80°C.

[0020] The second invention object of the present invention is to provide a bimetallic MOF material prepared by the above preparation method, wherein the bimetallic MOF material has a micro-nano porous structure, and the surface is rich in hydroxyl, amino, lanthanum ion and iron ion active sites, and the specific surface area is 100-300m 2 / g.

[0021] The third object of the present invention is to provide the application of the above bimetallic MOF material in removing and detecting fluoride ions in water.

[0022] In a further embodiment, the maximum adsorption capacity of the bimetallic MOF material for fluoride ions in water reaches 400.860 mg / g, and the linear detection range of the bimetallic MOF material for fluoride ion fluorescence detection is 0 to 80 μM.

[0023] The bimetallic MOF material prepared by the present invention has a rich surface of hydroxyl active groups and amino groups, and the active sites of iron ions and lanthanum ions are fully exposed, which can achieve rapid adsorption and capture of fluoride ions. It has a high adsorption capacity for fluoride ions in water, and its maximum adsorption capacity reaches 400.860 mg / g.

[0024] The bimetallic MOF material prepared in the present invention has been verified to have a sensitive detection capability for fluoride ions, with a linear range detection limit of 0 to 80 μM, and the fluorescence intensity is largely unaffected by other anions, thus showing good selectivity. These results confirm its significant fluorescence sensing performance in fluoride monitoring.

[0025] After the bimetallic MOF material is regenerated, the adsorbent can still maintain a stable and efficient fluoride ion removal rate, showing good regenerative properties. In addition, the bimetallic MOF material also has a strong ability to resist interference from impurity ions. In the actual industrial wastewater treatment effect test, the material can effectively adsorb and remove fluoride ions with an initial concentration of about 9 mg / L, reducing its concentration to below the drinking water standard (1 mg / L).

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The iron and lanthanum bimetallic MOF material synthesized by the preparation method of the present invention has a surface rich in hydroxyl and amino active groups, as well as iron and lanthanum metal ion active sites, and is fully exposed, which can achieve rapid adsorption and capture of fluoride ions, thereby simultaneously achieving the removal and detection of fluoride ions in water; the bimetallic MOF material has good reproducibility, anti-interference and stability, and the metal ion leaching is small and will not cause secondary pollution to the water body.

[0028] (2) The present invention uses organic lanthanum salts and organic iron salts to provide cations for the MOF organic framework, making the material more stable and able to expose more active sites, which is beneficial to improving the detection and adsorption performance of fluoride.

[0029] (3) The iron and lanthanum bimetallic MOF material synthesized in the present invention has a very high adsorption capacity, with a maximum adsorption capacity of 400.860 mg / g. In the effect test of treating actual industrial wastewater, it can adsorb and remove fluoride ions with an initial concentration of about 9 mg / L in water, reaching the drinking water standard of less than 1 mg / L.

[0030] (3) The iron and lanthanum bimetallic MOF material synthesized by the present invention has a sensitive detection capability for fluoride ions, and the linear range detection limit for fluoride ions is 0 to 80 μM. Moreover, its fluorescence intensity is largely unaffected by the presence of other anions, and has good selectivity for fluoride detection. Thus, the shortcomings of the instrumental analysis method for fluoride ion detection, such as high cost and complicated operation, are overcome, and a feasible solution is provided for the practical application of fluoride ion instant detection.

[0031] (4) The synthesis method and process used in the present invention are simple and easy to operate, avoiding the need for oven heating in traditional MOFs, and are suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the bimetallic MOF material prepared in Example 1 of the present invention;

[0033] Figure 2 This is a diagram showing the adsorption effect of the bimetallic MOF material prepared in Example 1 of the present invention on fluoride ions at different pH values;

[0034] Figure 3 The test results of the cycle performance of the bimetallic MOF material prepared in Example 1 of the present invention are as follows;

[0035] Figure 4 The fluorescence emission spectra of the bimetallic MOF material prepared in Example 1 of the present invention at different fluorine concentrations;

[0036] Figure 5 This is a concentration dependence relationship diagram of the fluorescence quenching behavior of the bimetallic MOF material prepared in Example 1 of the present invention in the presence of fluorine, which is fitted according to the Stern-Volmer (SV) equation. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0039] Example 1

[0040] A method for preparing an iron and lanthanum bimetallic MOF material comprises the following steps:

[0041] S1. Disperse lanthanum isopropoxide, ferrocenecarboxylic acid, and 2-aminoterephthalic acid in a molar ratio of 1:2:3 (0.316 g of lanthanum isopropoxide, 0.460 g of ferrocenecarboxylic acid, and 0.543 g of 2-aminoterephthalic acid) in 60 mL of DMF, and stir to mix uniformly to obtain a mixed solution;

[0042] S2, adding 3 mL of ammonia water to the mixed solution to adjust the pH of the mixed solution to 7-8; then performing ultrasonic treatment for 30 min to obtain a precursor;

[0043] S3, putting the precursor into a reactor and heating it in a 120°C oil bath for 12 hours, and cooling it naturally after the reaction is completed;

[0044] S4. Separate and extract the cooled reactants by centrifugation, dry them at 60° C., and grind them into powder to obtain an iron-lanthanum bimetallic MOF material.

[0045] The morphology of the iron and lanthanum bimetallic MOF material prepared in Example 1 was characterized by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the prepared material is a spindle-shaped nanostructure.

[0046] Application Example 1

[0047] The iron and lanthanum bimetallic MOF material prepared in Example 1 was used as an adsorbent to adsorb and remove fluoride ions:

[0048] Add 50 mL of fluorine-containing solution (fluorine ion concentration is 9 ppm) to a 100 mL conical flask, and adjust the initial pH value of the fluorine-containing solution to 2-11 with 0.5 mol / L NaOH or HCl solution; then add 0.025 mg of adsorbent (the bimetallic MOF material prepared in Example 1), and ultrasonicate for 1 min to evenly disperse the adsorbent. Place the conical flask in a 25°C constant temperature water bath shaker and shake for 24 h until the fluoride ions reach adsorption-desorption equilibrium. Take 1 mL of sample with a disposable syringe, filter to remove the adsorbent, and use an ion chromatograph to analyze the fluoride ion concentration in the sample (the fluoride ion concentration is below 0.5 mg / L, meeting the drinking water standard).

[0049] The results are as follows Figure 2 As shown, the adsorption rate of fluoride ions by the bimetallic MOF material reaches 96%, and it can effectively adsorb and remove fluoride ions in a wide pH range.

[0050] According to the above experimental method, after the adsorption experiment is completed, the solution is simply filtered to separate the solid adsorbent, and then 0.5 mol / L NaOH is used as the desorption liquid to regenerate the solid adsorbent, and then washed with deionized water to neutrality and fully dried to obtain the regenerated adsorbent. The regenerated adsorbent is then tested for recycling according to the above experimental method. The results are as follows: Figure 3 After 5 cycles, the removal rate of fluoride ions by the adsorbent was still above 90%.

[0051] Application Example 2

[0052] The iron and lanthanum bimetallic MOF material prepared in Example 1 was used as a fluorescent detector to detect the fluoride ion content:

[0053] 0.025 mg of the detection agent (the bimetallic MOF material prepared in Example 1) was added to 50 mL of a fluorine-containing solution with a fluoride ion concentration of 0 to 80 μM. The fluorescence intensity was analyzed by fluorescence emission spectroscopy and the concentration dependence of the fluorescence quenching behavior of the iron and lanthanum bimetallic MOF materials in the presence of fluorine was analyzed by fitting the Stern-Volmer (SV) equation. The results are as follows: Figure 4 , 5 The bimetallic MOF material has a sensitive detection capability for fluoride ions, with a linear detection range of 0 to 80 μM and a theoretical detection limit of 12.10 μM, providing a feasible solution for the practical application of real-time detection of fluoride ions.

[0054] in Figure 4 is the fluorescence emission spectrum obtained under different fluoride ion concentrations. - With the increase of concentration, the fluorescence intensity at 456 nm is constantly increasing, indicating that fluoride ions have an obvious fluorescence enhancement effect on the bimetallic MOF material prepared in the present invention.

[0055] Figure 5 It is quantitatively evaluated according to the Stern-Volmer (SV) equation.

[0056] I / I o =1+K SV C

[0057] Where, I: is the fluorescence intensity measured at 456nm after the ion F- to be tested is added to the suspension of NH2-MIL-101(Fe), I o : Fluorescence intensity measured at 456 nm when fluoride ions are not added to the suspension; C is the concentration of fluoride ions after the suspension is mixed with the fluoride ion solution; K SV is the quenching coefficient.

[0058] exist Figure 5 In the fluoride ion concentration range of 0 to 80 μM, the SV equation showed excellent linear correlation, R 2 It reaches 0.998, which shows that the material synthesized in this experiment has excellent sensitivity to fluoride ions.

[0059] Example 2

[0060] A method for preparing an iron and lanthanum bimetallic MOF material comprises the following steps:

[0061] S1, disperse lanthanum acetylacetonate, ferric holly acid, and 2-aminotricromellitic acid in 50 mL of DMF at a molar ratio of 2:1:3 (0.872 g of lanthanum acetylacetonate, 0.489 g of ferric holly acid, and 0.630 g of 2-aminotricromellitic acid), and stir to mix to obtain a mixed solution;

[0062] S2, adding 5 mL of ammonia water to the mixed solution to make the pH of the mixed solution 7-8; then performing ultrasonic treatment for 240 min to obtain a precursor;

[0063] S3, putting the precursor into a reactor, and heating it in an 80°C oil bath for 24 hours, and cooling it naturally after the reaction is completed;

[0064] S4. The reactants are separated and extracted after cooling by centrifugation, dried at 60° C., and then ground into powder to obtain an iron-lanthanum bimetallic MOF material.

[0065] Similar to Application Examples 1 and 2, the bimetallic MOF material prepared in Example 2 was tested on an actual fluoride-containing water sample, and the results showed that the bimetallic MOF material was able to reduce the initial fluoride concentration of 5 mg / L to below 0.5 mg / L, meeting the drinking water standard. It also had a sensitive detection capability for fluoride ions in the range of 0 to 60 μM fluoride ion concentration.

[0066] Example 3

[0067] A method for preparing an iron and lanthanum bimetallic MOF material comprises the following steps:

[0068] S1, lanthanum isopropoxide, ferrocenecarboxylic acid, and 2-aminoterephthalic acid are dispersed in 55 mL of ethylene glycol at a molar ratio of 1:3:4 (0.316 g of lanthanum isopropoxide, 0.69 g of ferrocenecarboxylic acid, and 0.725 g of 2-aminoterephthalic acid), and stirred to mix uniformly to obtain a mixed solution;

[0069] S2, adding 2 mL of sodium hydroxide solution to the mixed solution to make the pH of the mixed solution 10-11; then performing ultrasonic treatment for 60 min to obtain a precursor;

[0070] S3, put the precursor into a reactor, heat it in a 90°C oil bath for 18 hours, and cool it naturally after the reaction is completed;

[0071] S4. The reaction product is separated and extracted by centrifugation after cooling, dried at 60°C and ground into powder to obtain the iron-lanthanum bimetallic MOF material.

[0072] Similar to Application Examples 1 and 2, the bimetallic MOF material prepared in Example 3 was tested on an actual fluoride-containing water sample, and the results showed that the bimetallic MOF material was able to reduce the initial fluoride concentration of 5 mg / L to below 0.5 mg / L, meeting the drinking water standard. It also had a sensitive detection capability for fluoride ions in the range of 0 to 70 μM fluoride ion concentration.

[0073] Example 4

[0074] A method for preparing an iron and lanthanum bimetallic MOF material comprises the following steps:

[0075] S1, disperse lanthanum acetylacetonate, ferric holly acid, and 2-aminotricromellitic acid in 50 mL of ethanol at a molar ratio of 1:1:2 (0.436 g of lanthanum acetylacetonate, 0.489 g of ferric holly acid, and 0.420 g of 2-aminotricromellitic acid), and stir to mix uniformly to obtain a mixed solution;

[0076] S2, adding 5 mL of ammonia water to the mixed solution to adjust the pH of the mixed solution to 7-9; then performing ultrasonic treatment for 120 min to obtain a precursor;

[0077] S3, put the precursor into the reactor, heat it in a 100°C oil bath for 8 hours, and cool it naturally after the reaction is completed;

[0078] S4. The reaction product is separated and extracted by centrifugation after cooling, dried at 60° C., and ground into 200 mesh powder to obtain an iron-lanthanum bimetallic MOF material.

[0079] Similar to Application Examples 1 and 2, the bimetallic MOF material prepared in Example 4 was tested on an actual fluoride-containing water sample, and the results showed that the iron and lanthanum bimetallic MOF material prepared in this example can reduce the initial fluoride concentration of 5 mg / L to below 1 mg / L, reaching the drinking water standard. It also has a sensitive detection capability for fluoride ions in the range of 0 to 90 μM fluoride ion concentration.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a bimetallic MOF material, characterized in that: The following steps are involved: S1, dispersing an organic lanthanum salt, an organic iron salt and an organic ligand in an organic solution, stirring and ultrasonicating to obtain a mixed solution; S2, adding alkali to the mixed solution, and then performing ultrasonic treatment to obtain a precursor; S3, heating the precursor in an oil bath, and cooling it naturally after the reaction is completed; S4. Separate, dry and grind the reactants into powder to obtain a bimetallic MOF material; the bimetallic MOF material has adsorption and fluorescence detection functions.

2. The preparation method according to claim 1, characterized in that: The organic lanthanum salt is at least one of lanthanum acetylacetonate and lanthanum isopropoxide; The organic iron salt is at least one of ferrocenecarboxylic acid and ferroholly acid; The organic ligand is at least one of 2-aminoterephthalic acid and 2-aminotrimesic acid.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the organic lanthanum salt, the organic iron salt and the organic ligand is 1-5:1-5:2-10.

4. The preparation method according to claim 1, characterized in that: The alkali is ammonia water or sodium hydroxide solution, and the pH value of the mixed solution is 7-11 after the alkali is added.

5. The preparation method according to claim 1, characterized in that: The organic solvent is DMF, ethanol and ethylene glycol.

6. The preparation method according to claim 1, characterized in that: In step S3, the oil bath is heated at a temperature of 80-120° C. for a time of 6-24 hours.

7. The preparation method according to claim 1, characterized in that: In step S4, the separation is performed by centrifugation, and the drying temperature is 60-80°C.

8. The bimetallic MOF material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The bimetallic MOF material has a micro-nano porous structure, and its surface is rich in hydroxyl, amino, lanthanum ion and iron ion active sites, with a specific surface area of ​​100-300m 2 / g.

9. The use of the bimetallic MOF material as claimed in claim 8, characterized in that: It is used to remove and detect fluoride ions in water.

10. The use according to claim 9, characterized in that: The maximum adsorption capacity of the bimetallic MOF material for fluoride ions in water reaches 400.860 mg / g, and the linear detection range of the bimetallic MOF material for fluoride ion fluorescence detection is 0 to 80 μM.

Citation Information

Cited By

  • Difunctional fluorescent probe adsorption material as well as preparation method and application thereof

    CN119455920A

  • A dual-function fluorescent probe adsorption material and its preparation method and application

    CN119455920B